Screening of Autochthonous Microbial Strains for the Bioremediation of Heavy Metals - Cristina Firincă; Iuliana Răut; Maria-Lorena Jinga; Luiza Capră; Diana Popa; Anda Maria Baroi; Lucian-Gabriel Zamfir; Ana-Maria Gurban; Maria-Luiza Jecu; Mihaela Doni; Radu Claudiu Fierăscu; Mariana Constantin; et al. (Proceedings, 2023)
Numerous economic and industrial activities release significant amounts of heavy metals into the environment, with varying levels of toxicity depending on the concentration of exposure [...]